Design collaborative filtering recommender systems to solve cold-start problem - Hasan Mohammad Yusuf (Nanyang Technological University, 2022)
Recommender systems are information filtering system that suggests items like movies, songs, products, etc to users. Collaboration filtering approaches are adversely affected by the cold start problem, which makes it difficult to propose items to new users or for new items with no ratings when the item is first launched or is never rated. As a result, the rating quality suffers. The sparsity of the rating matrix is also a significant issue, as it makes it difficult to identify items that are related to one another and are similar. Many techniques have been presented, all of which rely on asking users to manually rate various items. These techniques might not have optimum performance if the user is not interested or refuses to provide ratings manually.